A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

Present-day glaciation in the South Shetland Islands - Orheim, Olav; Govorukha, Leonid Sergeevich (Annals of Glaciology, 1982)
Publisher: Cambridge University Press
Keywords: Antarktis; firnsnø; forskning; glasiologi; isbreer; stratigrafi; vulkaner

Basic volcanic rocks and tectonic setting. A discussion of the Zr-Ti-Y discrimination diagram and its suitability for classification purposes - Prestvik, Tore (Lithos, 1982)
Keywords: Bouvetøya; forskning; geologi; tektonikk; vulkaner

The geology, volcanic activity, and age of Bouvetøya, South Atlantic - Prestvik, Tore (Norwegian Antarctic Research Expeditions (1978/79), 1982)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi; vulkaner

The seismicity of the Bouvetøya region - Bungum, Hilmar; Kristoffersen, Yngve; Nilsen, Alf K. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; seismologi; vulkaner

Geology of Bouvetøya, South Atlantic - Prestvik, Tore; Winsnes, Thore S. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geologi; vulkaner